Enhancing Speaking Skills through Storytelling Method in Indonesian Language Learning: A Quasi-Experimental Study - Abdollah Thaib Nasution; Sutikno; Rahmat Kartolo (International Journal of Educational Research Excellence, 2026)
This study aims to determine the effect of the storytelling method on improving students’ speaking skills in Indonesian language learning. The research subjects were 36 fifth-grade students at SD S 117 Islam Terpadu Adnani, Mandailing Natal Regency, in the 2025/2026 academic year. The research employed a quantitative approach with a quasi-experimental design using a one-group pretest-posttest model. The instrument used was a speaking skills test covering aspects such as speaking confidence, fluency in storytelling, story structure, and the ability to convey moral messages. The results showed that the average pretest score for students' speaking skills before the application of the storytelling method was 65, categorized as moderate. After several learning sessions using the storytelling method, the posttest average score increased to 82, indicating a significant improvement in students' speaking skills. Inferential statistical analysis using a ttest showed that tcalculated > ttable, with a tcalculated value of 13.92 and a ttable value of 2.030 at a significance level of 0.05 with 35 degrees of freedom. Therefore, H₀ is rejected and H₁ is accepted, indicating a significant effect of the storytelling method on improving students’ speaking skills. More specifically, improvements were observed in several aspects: speaking confidence increased from 58% to 86%, fluency from 62% to 88%, story structure from 61% to 85%, and the ability to deliver moral messages from 59% to 84%. These findings demonstrate that storytelling as a learning method creates an active and enjoyable classroom atmosphere and encourages students to participate actively in developing comprehensive speaking skills. It can be concluded that the storytelling method is effectively used in Indonesian language learning to enhance the speaking skills of elementary school students